2020
DOI: 10.1016/j.ijpara.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Development of caecaloids to study host–pathogen interactions: new insights into immunoregulatory functions of Trichuris muris extracellular vesicles in the caecum

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Consequently, organoids have enabled previously unseen progress in many fields, one of them being infection biology, in particular for bacteria and viruses [reviewed in Hill and Spence (2017) and Artegiani and Clevers (2018) ]. The organoid model has enabled advances in the field of parasitology with infection studies on Cryptosporidium ( Heo et al, 2018 ; Wilke et al, 2019 ), T. gondii ( Derricott et al, 2019 ; Luu et al, 2019 ; Martorelli Di Genova et al, 2019 ), G. duodenalis ( Kraft et al, 2020 ) and helminths ( Eichenberger et al, 2018 ; Duque-Correa et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, organoids have enabled previously unseen progress in many fields, one of them being infection biology, in particular for bacteria and viruses [reviewed in Hill and Spence (2017) and Artegiani and Clevers (2018) ]. The organoid model has enabled advances in the field of parasitology with infection studies on Cryptosporidium ( Heo et al, 2018 ; Wilke et al, 2019 ), T. gondii ( Derricott et al, 2019 ; Luu et al, 2019 ; Martorelli Di Genova et al, 2019 ), G. duodenalis ( Kraft et al, 2020 ) and helminths ( Eichenberger et al, 2018 ; Duque-Correa et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has demonstrated the possibility to recapitulate complex life cycles of eukaryotic parasites. This is the case for Cryptosporidium parvum and Trichuris muris, which were studied using adult stem-cell-derived human and mouse intestinal organoids, respectively, grown in 3D (Heo et al, 2018;Duque-Correa et al, 2020). Cryptosporidium parvum could also be studied on intestinal monolayers at an air-liquid interface (Wilke et al, 2019) and had recently been transferred to an intestine-on-a-chip device, paving the way for long-term studies (Nikolaev et al, 2020).…”
Section: Pathogen Replication and Life Cyclementioning
confidence: 99%
“…Eichenberger et al (2018) showed that T. muris ELVs could be internalized by mouse colonic organoids raising the possibility of the ELVs communicating with intestinal epithelial cells. Duque-Correa et al (2020) developed a novel caecaloid model micro-injected with T. muris adult-derived ELVs which enabled study of the host pathogen interaction in vitro. Their study argues that the caecum is a unique and different niche to the colon and so provides additional and novel data to that provided in Eichenberger et al (2018).…”
Section: Exosomes and Exosome-like Vesiclesmentioning
confidence: 99%